Post-liver transplant biliary complications - K. O. Semash (Вестник трансплантологии и искусственных органов)
Biliary complications (BCs) are the most frequent complications following liver transplantation (LT). They are a major source of morbidity after LT. The incidence of BCs after LT is reported to range from 5% to 45%. The main post-LT biliary complications are strictures, biliary fistulas and bilomas, cholelithiasis, sphincter of Oddi dysfunction, hemobilia, and mucocele. Risk factors for biliary complications are diverse. In this article we seek to review the main types of biliary complications and modern approaches to their diagnosis and treatment.